2016
DOI: 10.1097/icb.0000000000000244
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Autofluorescence in Bilateral Diffuse Uveal Melanocytic Proliferation Associated With Esophageal Carcinoma and Choroidal Metastasis

Abstract: Bilateral diffuse uveal melanocytic proliferation can be associated with esophageal carcinoma as a systemic malignancy. Near-infrared imaging can be helpful to detect early stages of BDUMP and can help offer recently reported treatment options at an early stage of disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
1
2
0
2
Order By: Relevance
“…AF has been used several times already in visualizing BDUMP. 2 , 3 , 9 , 10 Our results also demonstrate and emphasize the ease with which AF can be used for diagnosis. We encourage an update to the diagnostic criteria wherein AF replace fluorescein angiography as the standard for appreciating the giraffe-pattern in BDUMP.…”
Section: Discussionsupporting
confidence: 57%
“…AF has been used several times already in visualizing BDUMP. 2 , 3 , 9 , 10 Our results also demonstrate and emphasize the ease with which AF can be used for diagnosis. We encourage an update to the diagnostic criteria wherein AF replace fluorescein angiography as the standard for appreciating the giraffe-pattern in BDUMP.…”
Section: Discussionsupporting
confidence: 57%
“…A recent study found multifocal ERG amplitudes within the lower reference range, recorded in the less affected eye of a patient with no exudative retinal detachment and normal autofluorescence, (Golshahi et al. ). The authors also reported patchy lesions in the same eye on near‐infrared autofluorescence.…”
Section: Diagnosismentioning
confidence: 98%
“… 2 , 7 , 8 , 9 Only 4% of uveal metastases arise from the gastrointestinal tract, and only a small percentage of these originate in the esophagus. 6 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 Furthermore, most reported cases of esophageal cancer metastasizing to the uvea are of squamous histology. Only a few cases of uveal metastases from adenocarcinoma of the esophagus have been reported in the literature.…”
Section: Discussionmentioning
confidence: 99%